Internal and external supervision in social work - outline framework for intervention in supervision - Vîșcu, Loredana-Ileana; Rad, Dana (Technium Education and Humanities, 2024)
This paper explores the evolving domain of supervision in social work, emphasizing the distinction between internal and external supervision and their implications for professional practice. Internal supervision involves supervisors embedded within organizations, navigating both managerial responsibilities and supervisory roles, while external supervision brings an independent perspective but is subject to organizational constraints. The framework for conducting effective supervision draws on the foundational work of Watkins, Cădariu, and Vișcu (2024) in psychotherapy supervision, adapted for the specific needs of social work. Key elements include the preparation of supervisors and supervisees, fostering positive supervisory relationships, and setting dynamic, collaborative objectives. The framework also highlights the importance of addressing power dynamics, multicultural considerations, and the professional development trajectories of supervisees. Practical implications extend to aligning supervision with organizational values, supporting psychotherapist-social workers, and enhancing resilience and adaptability in the social work field. The study advocates for structured, competency-based training programs for supervisors to ensure ethical, culturally sensitive, and effective supervision practices. Recommendations for future research include examining the long-term impacts of structured supervision frameworks and integrating digital tools into supervisory practices to address the challenges of hybrid and remote environments.